The influence of the cation structure on the basicity-related polarity of ionic liquids. Issue 47 (30th November 2021) - Weiß, Nadine; Thielemann, Gabi; Nagel, Kevin; Schmidt, Caroline H.; Seifert, Andreas; Kaßner, Lysann; Strehmel, Veronika; Corzilius, Björn; Schröder, Christian; Spange, Stefan
Abstract : The solvatochromic ThTCF probe responds to anion coordination. Correlations of UV/Vis data from ThTCF with various basicity-related polarity scales (Kamlet-Taft β, Freire E HB, Laurence β 1 ) allow an evaluation of their physical significance. Abstract : UV/Vis absorption data of ( E )-4-(2-[5-4, 4, 5, 5-tetramethyl-1, 3, 2-dioxaborolane-2-ylthiene-2-yl]vinyl)-2-(dicyano-methylene)-3-cyano-5, 5-dimethyl-2, 5-dihydrofuran (ThTCF ) as a solvatochromic probe is applied to examine the anion coordination strength ( e.g. of N(CN)2, BF4, PF6, N(Tf)2, CF3 COO) as a function of the cation structure of ionic liquids. Several 1- n -alky-3-methylimidazolium- and tetraalkylammonium CH3 -NR3 + -based ILs with different n -alkyl chain lengths (R = –C4 H9, –C6 H11, –C8 H17, –C10 H21 ) are considered. UV/Vis absorption data of ThTCF show subtle correlations with hydrogen bond accepting (HBA) ability-related measurands such as Kamlet–Taft β, Freire's E HB, and Laurence β 1 parameter as a function of anion and cation structure. The different influence of the n -alkyl chain length of imidazolium- and tetraalkylammonium-based ILs on the dipolarity and HBA strength is confirmed by comparison with the 14 N isotropic hyperfine coupling constants ( A iso ) of a positively (CATI ) and negatively charged spin probe (TSKCr ) of TEMPO-type [(2, 2, 6, 6-tetramethylpiperidin-1-yl)oxyl] and quantum chemically derived dipoles of the cations. The A iso values correlate with the absorption energy of ThTCF and E HB, but in different ways depending on the anion or charge of the spin probe. In a final discussion of the β, E HB, and β 1 scales in relation to ThTCF, the importance of the molar concentration N of ionic liquids for the physical significance of the respective parameters is discussed.